h y Saskia Van Genugten. - Van Genugten, Saskia; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Libya has a short, volatile history. Foreigners played a significant role in shaping Libya$1 (Bs institutions and policies, and this book explores longer term trends in the relations between Libya and the West, placing current developments in their historical context. Throughout history, the globe$1 (Bs most powerful actors have regarded Libya as an outlier state of little significance. Libya belonged neither here nor there and never fell under the full protection of any significant global or regional powerhouse. Libya$1 (Bs weak national identity, its weak institutions and its peripheral position have made it vulnerable to external influences and interventions. As a result, Libya repeatedly falls prey to foreign powers wanting to flex their muscles. As this book narrates, this was the case in 1911, in 2011 and several times in between.s
Keywords: History; History, Modern; Africa, North -- History; Military history; History; History of North Africa; Modern History; History of Military; Electronic books